Effect of The Atherogenic Index of Plasma on Microvascular Complications Associated with Type 2 Diabetes Mellitus - Hande Atalay; Banu Böyük; Şerife Değirmencioğlu; Savaş Güzel; Aslan Çelebi; İsmail Ekizoğlu (İstanbul Medical Journal, 2015)

(untitled)
Objective: The aim of this study was to evaluate the effects of the atherogenic index of plasma (AIP) on the microvascular complications of type 2 diabetes mellitus (DM) patients who applied to our internal medicine clinic.Methods: The study included 212 type 2 DM patients and 34 healthy controls who were compatible according to age and sex. Age, sex, duration of illness, treatment for diabetes and other illnesses associated with diabetes, height, weight, retinopathy, nephropathy, neuropathy, hypertension, and hyperlipidemia were recorded at the beginning of the study. AIP is calculated as the logarithm of the ratio between the triglyceride value and high density lipoprotein value (in mg/dL).Results: AIP and triglyceride levels of the type 2 DM patients were higher than those of the control group. Also, the study determined that 25.7% of the patients have retinopathy, 31.6% have neuropathy, 29.1% have microalbuminuria, and 3.9% have macroalbuminuria. If we accept that there is a complications who have one of these complications in this three, there is 62.6% of the patients have complications. A statistically significant correlation was determined with these complications and lipid subgroups such as AIP and low density lipoprotein (LDL).Conclusion: The relationship between AIP and only nephropathy, which is a complication in type 2 DM patients, was determined.